2005
DOI: 10.1172/jci200522365
|View full text |Cite
|
Sign up to set email alerts
|

The MODY1 gene HNF-4α regulates selected genes involved in insulin secretion

Abstract: Mutations in the gene encoding hepatocyte nuclear factor-4α (HNF-4α) result in maturity-onset diabetes of the young (MODY). To determine the contribution of HNF-4α to the maintenance of glucose homeostasis by the β cell in vivo, we derived a conditional knockout of HNF-4α using the Cre-loxP system. Surprisingly, deletion of HNF-4α in β cells resulted in hyperinsulinemia in fasted and fed mice but paradoxically also in impaired glucose tolerance. Islet perifusion and calcium-imaging studies showed abnormal resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
159
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(174 citation statements)
references
References 56 publications
11
159
0
4
Order By: Relevance
“…HNF4␣ is highly expressed in liver, kidney, intestine, and pancreas, and its crucial role in liver and endocrine pancreas has been demonstrated by genome-wide expression profiling (2) and conditional deletion in mice (3)(4)(5)(6). In addition, dysfunction of HNF4␣ is associated with various metabolic disorders, and mutations in HNF4␣ cause a dominantly inherited form of diabetes referred to as MODY1 (maturity-onset diabetes of the young) (7).…”
Section: Hepatocyte Nuclear Factor 4␣ (Hnf4␣)mentioning
confidence: 99%
“…HNF4␣ is highly expressed in liver, kidney, intestine, and pancreas, and its crucial role in liver and endocrine pancreas has been demonstrated by genome-wide expression profiling (2) and conditional deletion in mice (3)(4)(5)(6). In addition, dysfunction of HNF4␣ is associated with various metabolic disorders, and mutations in HNF4␣ cause a dominantly inherited form of diabetes referred to as MODY1 (maturity-onset diabetes of the young) (7).…”
Section: Hepatocyte Nuclear Factor 4␣ (Hnf4␣)mentioning
confidence: 99%
“…Clinical researches have indicated that mutations in gene encoding HNF4α result in maturityonset diabetes of the young type 1, characterized by autosomal dominant inheritance, early onset and impairment of glucose-stimulated insulin secretion (GSIS) [11] . And two independent laboratory studies demonstrated that β-cell-specific HNF4α knock-out mice exhibited impaired GSIS and deficient intracellular calcium response to glucose or SU [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Decreased activity of K ATP or Kv2.1 in islets increases insulin secretion (19), suggesting that these channels may mediate propafenone's effects on insulin secretion. Although amiloride and propafenone have not been previously studied in the context of HNF4α, SCNN1A (encoding the target of amiloride) and KCNJ11 (encoding Kir6.2, a subunit of K ATP ) are among the hundreds of reported transcriptional targets of HNF4α (though data on the dependence of KCNJ11 expression on HNF4α in vivo are conflicting) (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…HNF4α binds to upstream sequences of hundreds of genes involved in glucose, lipid, cholesterol, amino acid, and drug metabolism (8)(9)(10). Two different conditional knockouts of HNF4α in β-cells yielded conflicting phenotypes: although both knockout models showed impaired insulin secretion in response to glucose challenge (11,12), one model also unexpectedly showed elevated resting insulin levels with associated hypoglycemia (12), highlighting our incomplete understanding of the physiologic effects of HNF4α mutation.…”
mentioning
confidence: 99%